2021
DOI: 10.1002/jia2.25814
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of antiretroviral therapy through private pharmacies and postal courier services during COVID‐19 in Botswana: acceptability and reach of two out‐of‐facility individual differentiated service delivery models

Abstract: IntroductionThe advent of COVID‐19 has put pressure on health systems as they implement measures to reduce the risk of transmission to people living with HIV (PLHIV) and healthcare workers. For two out‐of‐facility individual differentiated service delivery (DSD) models, we assessed acceptability of antiretroviral therapy (ART) distribution through private pharmacies and reach of home delivery of ART through courier services during the COVID‐19 pandemic in Botswana.MethodsFrom 24 July to 24 August 2020, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…The eight additional studies found that the delivery of ART services at private pharmacies was largely feasible and acceptable [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Three pilot studies in Uganda and Nigeria that assessed the feasibility of pharmacy‐delivered ART refills found that the majority (>90%) of ART clients chose this option and refilled on schedule [ 49 , 51 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The eight additional studies found that the delivery of ART services at private pharmacies was largely feasible and acceptable [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Three pilot studies in Uganda and Nigeria that assessed the feasibility of pharmacy‐delivered ART refills found that the majority (>90%) of ART clients chose this option and refilled on schedule [ 49 , 51 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of in‐depth interviews with stakeholders in South Africa reported that private pharmacies were an instrumental and underexplored component of differentiated HIV service delivery [ 50 ]. In acceptability studies in South Africa and Botswana, ART clients reported that they would be willing to pay for pharmacy‐delivered ART refills [ 57 ], most found these services to be quicker and more convenient than clinic‐delivered refills [ 53 ], and many indicated that this model fit their values, preferences and needs [ 55 ]. However, some clients were concerned with inadvertent disclosure of their HIV status when pharmacy providers refill ART [ 53 ] and potentially lower‐quality communication, education and emotional support received with the delivery of ART refills at pharmacies versus clinics [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations